KONTRIBUSI KEGIATAN EKSTRAKURIKULER KARATE DALAM PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Nurul Isnaeni, Hesti (Penerbit CV Tentrem Karya Nusa, 2019)
Abstract: This study aims to observe the contribution of karate extracurricular activities to (towards) building students disciplinary and responsible character in MI Darul Hikmah Bantarsoka, West Purwokerto District, Banyumas Regency. This research is a field research, which type is qualitative. The techniques used to collect the data are by observation, interviews, and documentation. The data obtained from the three data collection techniques are then collected through triangulation of techniques and sources. From the results of the analysis conducted by karate extracurricular activities have a positive contribution to building students? disciplinary and responsible character the character of discipline and responsibility MI Darul Hikmah Bantarsoka, West Purwokerto District, Banyumas Regency. Students who take part in karate extracurricular activities have those two positive characters. The disciplinary attitude of students can be seenthrough several activities such as: religious discipline, time discipline, discipline towards regulations, discipline of learning, and discipline in attitude. The character of the responsibilities of the students includes the responsibility of being exposed to the densiri, family, community, nation and state and God AlmightyKey Words: Karate extracurricular activity, Discipline Character and Responsibility